2015
DOI: 10.1371/journal.pone.0134742
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucans (Saccharomyces cereviseae) Reduce Glucose Levels and Attenuate Alveolar Bone Loss in Diabetic Rats with Periodontal Disease

Abstract: The objective of this study was to assess the effects of oral ingestion of β-glucans isolated from Saccharomyces cereviseae on the metabolic profile, expression of gingival inflammatory markers and amount of alveolar bone loss in diabetic rats with periodontal disease. Diabetes mellitus was induced in 48 Wistar rats by intraperitoneal injection of streptozotocin (80 mg/kg). After confirming the diabetes diagnosis, the animals were treated with β-glucans (by gavage) for 28 days. On the 14th day of this period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 44 publications
4
35
0
1
Order By: Relevance
“…A beneficial effect in the glycemic control, in our study, was also observed after beta-glucan ingestion, as reported elsewhere in both animal [10] and in human studies [36]. Blood glucose control by beta-glucan consumption is probably due to the fact that these fibers form a gelatinous barrier in the intestinal lumen, hindering the absorption of carbohydrates and lipids by enterocytes [10,37,38]. In this sense, the same mechanism can be used to justify a reduction in circulating levels of total cholesterol, LDL-C and TAG found in groups treated with beta-glucan, with and without exercise.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A beneficial effect in the glycemic control, in our study, was also observed after beta-glucan ingestion, as reported elsewhere in both animal [10] and in human studies [36]. Blood glucose control by beta-glucan consumption is probably due to the fact that these fibers form a gelatinous barrier in the intestinal lumen, hindering the absorption of carbohydrates and lipids by enterocytes [10,37,38]. In this sense, the same mechanism can be used to justify a reduction in circulating levels of total cholesterol, LDL-C and TAG found in groups treated with beta-glucan, with and without exercise.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, this effect is due to the increased glucose uptake by skeletal muscle during exercise and increased insulin sensitivity for some hours after physical activity [35]. A beneficial effect in the glycemic control, in our study, was also observed after beta-glucan ingestion, as reported elsewhere in both animal [10] and in human studies [36]. Blood glucose control by beta-glucan consumption is probably due to the fact that these fibers form a gelatinous barrier in the intestinal lumen, hindering the absorption of carbohydrates and lipids by enterocytes [10,37,38].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Beta-glucans have been widely used in research for medical purposes (King et al, 2005;Sener et al, 2006;Harnack et al, 2011;Vetvicka 2011;Samuelsen et al, 2014;Chen et al, 2013;Tosh, 2013;Silva et al, 2015). These are polysaccharides from the cell wall of a variety of plants, fungi, yeasts, algae and some bacteria.…”
Section: Introductionmentioning
confidence: 99%